Two-Step Facile Preparation of 2D MoS2/ZnO Nanocomposite p-n Junctions with Enhanced Photoelectric Performance - Ali Aldalbahi; Zhen-Bo Wang; Tansir Ahamad; Saad M. Alshehri; Peter X. Feng (International Journal of Photoenergy)
Both p-n and n-p heterojunctions of ZnO-MoS2 have been fabricated in order to understand the performance of electron and hole transport properties in solar cells and a self-powered photodetector system. Atomically thin 2-dimensional (2D) MoS2 was prepared by using a spin coating method with controlled process times, whereas ZnO nanowires were prepared by using a plasma sputtering deposition technique. The nanoscale morphologies, composites, and photoelectric properties of nanocomposites were examined using scanning electron microscopy, energy-dispersive X-ray spectroscopy, and micro-Raman scattering spectroscopy, respectively. 2D heteronanostructures have exhibited an enhanced performance as compared to single-material-based prototypes. In photovoltaic mode, n-p heterojunction of the ZnO-MoS2-based prototype appears to have much better photoelectric conversion efficiency than that in the case with p-n junction, indicating highly effective hole transport properties of 2D MoS2 materials. Both band broadening and band shift were observed. Furthermore, the bias, annealing, and synergistic effects on the generated photocurrents and the response times were evaluated. The newly designed prototype exhibits exceptional properties: a broadband spectral response, a high signal-to-noise ratio, and excellent stability.